Virtual Reality Heights Exposure and Its Impact on College Student’s Physiological Response and Emotional Condition - Brillianda Resibisma; Neila Ramdhani (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Various studies have been done to overcome excessive fear of heights. One way to overcome excessive fear of heights is to use exposure therapy. This study aimed to determine the effect of virtual reality heights exposure on physiological response and emotional condition in college students. The hypothesis of this study was that there is a significant effect of virtual reality heights exposure on physiological response and emotional condition that is characterized by changes in skin conductance when the stimulus is presented and changes in emotional condition after the stimulus is presented. The design applied in this study was a non-random pretest and posttest experiment. The results of this study indicated that there is a significant influence of virtual reality exposure on physiological response and emotional condition. Thus, the finding opens up opportunities for therapy using this method in Indonesia.